(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The study aims to investigate the indicator path from the sentence of the Constitutional Court n. 242/2019 on medically assisted suicide. Pending the approval of the legislative discipline, on which Parliament is currently working, deemed necessary by the Constitutional Court itself to give certainty to such an ethically delicate matter, judges are increasingly finding themselves deciding on cases of medically assisted suicide and both on the level of criminal law and on the level of civil law, interpreting the constitutional jurisprudence on the subject in a constitutionally compliant.